Effects of Minocycline as a Neuroprotective Agent for Stroke on Mmp-9 Levels, Functional Outcome, and Mortality - Nisa, Ayu Imamatun; Damayanti, Arlia Ayu; Nagasastra, Jeffri; Machin, Abdulloh; Qorib, Mohammad Fathul; , Retnaningsih; Hamidi, Baarid Luqman (Folia Medica Indonesiana, 2024)
Highlights: 1. As minocycline plays an important role in stroke microglia activation and iron chelation, it is important to further analyze its effects on stroke treatment. 2. This meta-analysis revealed a significant effect of minocycline therapy, as evidenced by improved functional outcomes and inhibited matrix metalloproteinase-9 (MMP-9) activity. Abstract Stroke is the most common and devastating cerebrovascular disease. Many neuroprotective medications, such as scale and minocycline, have been developed to help the nervous system recover or regenerate after a stroke. However, it remains unclear whether minocycline provides a beneficial effect on stroke. We conducted this systematic review and meta-analysis to synthesize the effects of minocycline in stroke treatment. The systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO), with registration number CRD42023485168. The quality of the eligible studies was assessed using the Jadad scale. This systematic review included three ischemic stroke trials, seven intracerebral hemorrhage trials, and one study on acute stroke. There was a significant association between minocycline intervention and stroke severity according to the National Institute of Health Stroke Scale (NIHSS), with a pooled mean difference (MD) of -1.92, a 95% confidence interval (CI) of -3.39 to -0.45, and a value of p=0.01. In the subgroup of ischemic stroke, the modified Rankin Scale (mRS) was significantly lower in the minocycline treatment group compared to the control group (MD=-0.89, 95% CI=-1.54 to -0.25, p=0.007). Additionally, matrix metalloproteinase-9 (MMP-9) levels for the intracerebral hemorrhage subgroup were significantly lower in the minocycline treatment group compared to the control group (MD=-19.93, 95% CI=-36.9 to -2.96, p=0.02). The analysis revealed that minocycline intervention was not significantly associated with hematoma volume, mortality, or stroke recurrence. Our findings indicate that minocycline supplementation is a potential intervention strategy for treating ischemic stroke and intracerebral hemorrhage.